Methods for evaluation of masticatory efficiency in conventional complete denture wearers: a systematized review - Oliveira Júnior, Norberto Martins de [UNESP]; Shaddox, Luciana Machion; Toda, Carina; Paleari, André Gustavo; Pero, Ana Carolina [UNESP]; Compagnoni, M. A. [UNESP] (My University, 2014)
The objective of this study was to present a systematized review of different methods used to evaluate the masticatory efficiency in conventional complete denture wearers. A survey was conducted in the databases PubMed, Scopus, and Cochrane, seeking scientific articles according to the previously selected terms: "Masticatory performance", "Masticatory efficiency" and "Chewing ability complete denture". Moreover, complementary studies have been carried out with library manual search/databases, which included studies related to different ways to assess masticatory efficiency, specifically as it related to conventional complete denture wearers. Forty three papers were selected to be used in the present review. Despite the wide variety of methodologies in the literature, the sieves method is currently considered the gold standard method to evaluation of conventional complete denture wearers masticatory efficiency, since it is the simplest, does not depend on specific devices (beyond the set of sieves), allows for a rational assessment, and it has been widely reproduced in various types of oral rehabilitation. More, the almond, as natural test food, and the optocal (made from the molding material Optosil), as artificial test food, are the most constantly employed test foods to evaluate masticatory efficiency.